B lymphocytes impair osteogenesis by inhibiting BMSC differentiation in osteoporosis - Cong Peng; Qiao Yang; Linyu Li; Yufeng Li; Zhaoyang Ye; Kun Zhao; Yi Yi; Liang Wang (Immunobiology)
Background: B lymphocytes have been implicated in the inhibition of osteogenesis, but their role in osteoporosis (OP) remains unclear. This study investigates the association between B lymphocytes and impaired osteogenesis in OP patients and explores the underlying mechanisms. Methods and materials: A retrospective analysis of 93 patients with OP assessed the relationship between B lymphocyte counts, bone formation marker Procollagen type I N-terminal propeptide (P1NP), and bone mineral density (BMD). An ovariectomy-induced OP mouse model was established. B lymphocytes and bone marrow mesenchymal stem cells (BMSCs) were isolated and co-cultured to evaluate the impact of B lymphocytes on osteogenic differentiation. Transcriptomic profiling and qPCR were performed to identify key regulatory genes. Results: Clinically, B lymphocyte counts were significantly elevated in OP patients with impaired osteogenesis (P < 0.05). Receiver operating characteristic (ROC) analysis indicated diagnostic potential (AUC = 0.638, P < 0.05). In vitro, B lymphocytes reduced Alkaline phosphatase (ALP) activity, calcium deposition, and the expression of osteogenic markers (Osterix, Cbfa1) in BMSCs. Transcriptomic analysis identified 210 differentially expressed genes, among which four (Ccdc170, Extl1, Smpd3, and Thsd4) were validated as potential mediators of B cell-induced osteogenesis inhibition. Conclusion: B lymphocytes may impair osteogenesis in OP by suppressing BMSC differentiation. These findings highlight B lymphocytes as potential diagnostic markers and therapeutic targets in osteoporosis.